The Dilemma of Australian Pacific Solution: The Non-Refoulement Principle Versus National Security - Ninin Ernawati (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
The Australian Government has issued various policies to deal with refugees. One of the policies is the Pacific Solution and it is considered as a manifestation of national security principles. On one hand, the policy against the non-refoulement principle, which is the central principle of the refugee convention and Australia is one of the states that ratified the 1951 Refugee Convention. Obviously, Australia should not violate the non-refoulement principle. On the other hand, Australia has experienced a dilemma between prioritizing its interests and fulfilling international obligation to protect refugees who entering its territory. This article discusses whether the national security principle is contrary to the non-refoulement principle; and how Australia can accommodate both principles without neglecting the rights of refugees and still be able to maintain their interests. This article also reviews how Australia can implement policies based on national security principle when it has to face international obligations–in this case, the non-refoulement principle. This research concludes that the national security and the non-refoulement principle are basically contradictory. However, Australia can accommodate these two principles by counterbalancing actions, such as the establishment of national laws that still highly consider humanitarian standards contained in the non-refoulement principle. Australia has the right to implement number of policies based on its national law, while that the same time Australia cannot ignore their international obligation to protect refugees in accordance with the 1951 Refugee Convention that they have ratified. Reflecting on some previous policies, this study concludes that Australia has not been able to accommodate both principles.Dilema “Australian Pacific Solution”: Prinsip Non-Refoulement berhadapan dengan Keamanan Nasional AbstrakPemerintah Australia telah mengeluarkan berbagai macam kebijakan untuk menangani kasus pengungsi. Salah satu kebijakannya adalah pacific solution. Kebijakan ini merupakan salah satu bentuk penerapan prinsip national security Australia. Di sisi lain, kebijakan ini dianggap melanggar prinsip non-refoulement, yang merupakan prinsip utama dalam konvensi pengungsi. Australia merupakan salah satu negara yang meratifikasi Konvensi Pengungsi 1951. Oleh karena itu, Australia seharusnya tidak melanggar prinsip Non-Refoulement tersebut. Dalam menanggapi permasalahan tersebut, selama ini Australia mengalami dilema di antara mengutamakan negaranya atau menunaikan kewajiban internasional untuk melindungi pengungsi yang memasuki batas lautnya. Artikel ini mendiskusikan apakah prinsip national security tersebut bertentangan dengan prinsip non-refoulement; dan bagaimana Australia bisa mengakomodasi kedua prinsip tersebut agar tidak menelantarkan hak-hak para pengungsi internasional dan tetap dapat melindungi kepentingan negaranya. Artikel ini juga akan mengulas bagaimana Australia dapat menerapkan kebijakan berdasarkan prinsip national security ketika harus menghadapi kewajiban internasional–dalam hal ini prinsip non-refoulement. Penelitian ini menyimpulkan bahwa prinsip national security dan prinsip non-refoulement pada dasarnya bertentangan. Akan tetapi, Australia dapat mengakomodasi kedua prinsip tersebut melalui tindakan penyeimbang, seperti pembentukan hukum nasional yang tetap memperhatikan standar kemanusiaan yang terkandung dalam prinsip non-refoulement. Australia berhak melaksanakan beberapa kebijakan yang tertuang dalam hukum nasional. Di sisi lain, Australia juga tidak dapat mengabaikan kewajiban internasional untuk melindungi pengungsi sesuai dengan Konvensi Pengungsi 1951 yang telah mereka ratifikasi. Berkaca pada beberapa kebijakan sebelumnya, kajian ini menyimpulkan bahwa Australia belum dapat mengakomodir kedua prinsip tersebut.Kata Kunci: Keamanan Nasional, Non-Refoulement, Pacific SolutionDOI: https://doi.org/10.22304/pjih.v6n2.a7